2017
DOI: 10.1136/bmjopen-2016-012851
|View full text |Cite
|
Sign up to set email alerts
|

UK parents’ attitudes towards meningococcal group B (MenB) vaccination: a qualitative analysis

Abstract: Objectives(1) To explore existing knowledge of, and attitudes, to group B meningococcal disease and serogroup B meningococcal (MenB) vaccine among parents of young children. (2) To seek views on their information needs.DesignCross-sectional qualitative study using individual and group interviews conducted in February and March 2015, prior to the introduction of MenB vaccine (Bexsero) into the UK childhood immunisation schedule.SettingCommunity centres, mother and toddler groups, parents’ homes and workplaces i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 24 publications
2
17
0
2
Order By: Relevance
“…The latter sources tend to report predominantly on the speculated negative outcomes of vaccines. This result is consistent with some other studies [2,3,18,20,21] which reported meningococcal vaccine side effects as the commonly stated reason for not having a child receive the vaccine. The safety of different types of the vaccine has been documented [42,43], therefore, improving communication tools—i.e., provision of adequate information by physicians or public health authorities—could raise parental awareness regarding this subject.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The latter sources tend to report predominantly on the speculated negative outcomes of vaccines. This result is consistent with some other studies [2,3,18,20,21] which reported meningococcal vaccine side effects as the commonly stated reason for not having a child receive the vaccine. The safety of different types of the vaccine has been documented [42,43], therefore, improving communication tools—i.e., provision of adequate information by physicians or public health authorities—could raise parental awareness regarding this subject.…”
Section: Discussionsupporting
confidence: 92%
“…The decision to immunize a child against N. meningitidis is affected by parental knowledge of the IMD, as well as their knowledge of the vaccine, and attitudes about its use [2,18]. Although numerous studies in different countries have investigated the N. meningitidis vaccine uptake, as well as knowledge of IMD and the acceptability of the vaccine among parents [2,19,20,21,22,23], surveys related to this issue are rather scant in Central Europe, including Poland.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, our study contributes novel and timely evidence to understand the need for greater parental awareness MenB vaccines, a topic for which there is very limited data. Previous studies investigating the willingness to receive MenB vaccines have been undertaken only in the context of an outbreak [ 24 ] or in countries outside the US where vaccination recommendations differ significantly [ 16 23 ]. We have provided evidence that awareness of MenB vaccine is lacking among parents of teens in the US and that awareness of MenB vaccines, along with concern for meningococcal disease, are important predictors of willingness to vaccinate with the newly licensed MenB vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing vaccine uptake and ensuring the sustainability of high uptake of both MenAWCY and MenB vaccines is critical to achieving this goal. While studies have been conducted in other countries to address knowledge and attitudes about the recently developed MenB vaccines [ 16 23 ], only one study has investigated awareness of MenB vaccine in the US [ 24 ]. Breakwell et al investigated uptake in the context of an ongoing MenB outbreak and found 51% MenB vaccine coverage among a college student population at a time when the vaccine was not yet licensed; vaccinees were motivated by the knowledge that meningitis is a serious disease and that vaccination is the best way to protect oneself [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In children aged <2 years, for example, fever rates were 44% lower when 4CMenB was given with paracetamol prophylaxiscompared with only a 22% reduction among children and adolescents aged 5–16 years 40. An attitudinal survey of UK parents found that the overwhelming majority would accept 4CMenB immunisation despite the high rates of fever because the fear of their child developing IMD was far worse than self-limiting postvaccination fever;41 most parents also had no concerns giving their infant prophylactic paracetamol to reduce the risk of vaccine-related adverse events 41. In the UK, prophylactic paracetamol is not recommended for the booster at 1 year because both parents and healthcare professionals expressed more confidence with managing fever and other vaccine-related reactions in the older infant.…”
Section: Introductionmentioning
confidence: 99%